Evaluation of Training Program of Health Volunteers and Covered Households of Urban Areas of Mamasani City Using Kirk Patrick Model at 2020 - Fariba Khanipoor; Abdolhasan Cheraghi; Leila Bazrafkan (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: It is necessary to change, modify, and evaluate educational programs over time. Due to the major role of education and the need to use effective and multifaceted evaluation methods, the present study aimed to assess the training courses of health volunteers according to the Kirkpatrick model. Methods: This quasi-experimental study was performed on 102 health volunteers in urban health centers in Mamasani city. The data collection tool was a two-part questionnaire, including demographic characteristics and evaluation of reaction levels, learning, performance, and results of training courses conducted for health volunteers and covered households. The data were analyzed in SPSS (version 25). Results: The level of desirability of the provided education was assessed by calculating the average scores of the desirability of the four levels. In the first level of the Kirkpatrick model, most volunteers and covered families were satisfied with participating in the training courses. At the second level, their knowledge increased significantly (P= 0.01). The average score in the field of behavior and performance of volunteers was 74.41%, and it was 74.44% in covered households. In the field of training results, the average score of health volunteers was 49.99%, and it was 49.96% in covered households, indicating the effective role of training and evaluation effectiveness. Conclusion: The evaluation of the educational program for health volunteers and covered households indicated the positive effect of the training provided to achieve the goals of the program. Due to the applicability of the health volunteer program at all levels of society, the use of a multidimensional model, such as Kirkpatrick, to evaluate this program and other educational programs of the health care system is recommended.